A Digital Microscopic Inspection of Dentinal Defects after Using Endodontic Retreatment Files. (8th February 2021) - AbuMostafa, Ammar; Almoqayyad, Hala; Mohammad, Al-Omari
Abstract : Aim . The study aimed at evaluating the incidence of dentinal defects after root canal retreatment with ProTaper Universal retreatment (PTUR) and XP-endo Shaper and Finisher R (XP). Materials and Methods . Sixty extracted single-rooted human premolars were selected and divided into 4 groups of 15 teeth each. In the negative control group, the teeth were left unprepared. In the positive control group, the teeth were prepared with ProTaper Next and obturated with no further retreatment. In the PTUR and XP groups, the teeth were prepared and obturated followed by removal of the filling material at body temperature using PTUR and XP instruments, respectively. The roots were then sectioned at 3, 6, and 9 mm from the apex and observed under a digital microscope to detect defects. Results . PTUR group showed significantly higher (p value <0.05) incidence of defects than the other groups. Comparison of no defects versus defects between groups in different areas of root canals demonstrated significant difference among the groups in the apical and cervical regions. Conclusion . Within the limitations of the present study, PTUR files created significantly more dentinal defects than XP files, with most of those defects at the cervical and apical areas of the root canals.